2006
DOI: 10.1007/s00122-005-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Advanced backcross QTL analysis of a hard winter wheat × synthetic wheat population

Abstract: Advanced backcross quantitative trait locus (AB-QTL) analysis was used to identify QTLs for yield and yield components in a backcross population developed from a cross between hard red winter wheat (Triticum aestivum L.) variety Karl 92 and the synthetic wheat line TA 4152-4. Phenotypic data were collected for agronomic traits including heading date, plant height, kernels per spike, kernel weight, tiller number, biomass, harvest index, test weight, grain yield, protein content, and kernel hardness on 190 BC2F(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(96 citation statements)
references
References 52 publications
11
77
2
6
Order By: Relevance
“…Their results confirm the relationship of the Xmta9 locus to Pin-a (Pina-D1) and the Xmta10 locus to Pin-b (Pinb-D1). Three further studies revealed significant QTL effects for grain hardness linked to Xmta9, Xmta10 and Xcfd18 at the Ha locus on the short arm of chromosome 5D, respectively (Sourdille et al 1996;Perretant et al 2000;Narasimhamoorthy et al 2006). At the QTL QGh.Z86-5D.a, the exotic allele led to softer grains, which was also discovered by Sourdille et al (1996) and the AB-QTL study of Narasimhamoorthy et al (2006).…”
Section: Grain Hardness (Gh)mentioning
confidence: 96%
See 1 more Smart Citation
“…Their results confirm the relationship of the Xmta9 locus to Pin-a (Pina-D1) and the Xmta10 locus to Pin-b (Pinb-D1). Three further studies revealed significant QTL effects for grain hardness linked to Xmta9, Xmta10 and Xcfd18 at the Ha locus on the short arm of chromosome 5D, respectively (Sourdille et al 1996;Perretant et al 2000;Narasimhamoorthy et al 2006). At the QTL QGh.Z86-5D.a, the exotic allele led to softer grains, which was also discovered by Sourdille et al (1996) and the AB-QTL study of Narasimhamoorthy et al (2006).…”
Section: Grain Hardness (Gh)mentioning
confidence: 96%
“…Altogether four AB-QTL analyses of wheat have been published so far (Huang et al 2003(Huang et al , 2004Narasimhamoorthy et al 2006;Liu et al 2006). In all cases, the synthetic exotic donor parent originated from hybridisation of durum with T. tauschii, thus lacking exotic alleles on genomes A and B.…”
Section: Qtl Analysis and Comparison With Candidate Genes And Other Qmentioning
confidence: 99%
“…Comparative analysis with the known major QTL for yield in wheat: A survey of the literature reporting QTL for GY and related agronomic traits in both tetraploid and hexaploid wheat (Li et al 2002;Peng et al 2003;Elouafi and Nachit 2004;Huang et al 2004Huang et al , 2006McCartney et al 2005;Quarrie et al 2005Quarrie et al , 2007Marza et al 2006;Narasimhamoorthy et al 2006;Kuchel et al 2007;Kumar et al 2007;Ma et al 2007) revealed rather different scenarios for the two major GY QTL identified in our study. Our comparative analysis was carried out by relating the (LOD À 1) supporting interval of the QTL to the Ta-SSR-2004 consensus map (Somers et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two parents tetraploid wheat and diploid Aegilops of artificially synthesized wheat carried disease-resistance gene and gene increasing yield [14]. When gene of artificially synthesized hexaploid wheat was introduced in common wheat, wheat quality and quantity was improved [13] [15]- [18]. In this study, parent Opata55 of ITMI population was a common Mexican wheat variety bred by CIMMYT and parent W7984 (M6) was an artificially synthesized variety cross-bred between Altar 84 (T. durum, AABB) and TA 2465 (Aegilops tauschii, DD) with chromosome doubling [19].…”
Section: Discussionmentioning
confidence: 99%